Severe idiopathic osteoporosis in a premenopausal woman: A case for dual therapy - Sudarsanababu Lalitha Soumya; Kripa Elizabeth Cherian; Nitin Kapoor; Thomas Vizhalil Paul (Wolters Kluwer Medknow Publications, 2020)
Currently available agents improve bone mineral density (BMD) values on their own in monotherapy but may not completely restore microarchitecture and the patient may continue to sustain fragility fractures. Current monotherapies can only address either increased bone resorption or decreased bone formation. In this setting, combination therapy with antiresorptive and anabolic agents appears to be a promising option. A 49-year-old premenopausal woman presented with severe low backache associated with significant height loss. Evaluation elsewhere revealed severe osteoporosis, which prompted treatment with three doses of parenteral zoledronate 4 mg annually, followed by oral alendronate 70 mg once weekly for 7 years. However, her symptoms persisted despite treatment, and investigations done at our center confirmed severe osteoporosis, with multiple vertebral compression fractures. She was initiated on teriparatide therapy but despite 1 year of treatment, there was persistent height loss. In addition, there was a marked elevation of bone resorption, which prompted us to add denosumab which was administered subcutaneously every 6 months. On follow-up, there was marked relief from pain, no further decrease in height, and progressive improvement in BMD, and bone turnover markers were noted. A dual therapy with anabolic agent teriparatide and antiresorptive agent denosumab for osteoporosis may be a viable option in individuals with severe osteoporosis who do not respond well to a single agent.